New Insights into Detection of a Dendrobine Compound From a Novel Endophytic Trichoderma longibrachiatum Strain and Its Toxicity Against Phytopathogenic Bacteria - Sarsaiya, Surendra; Jain, Archana; Fan, Xiaokuan; Jia, Qi; Xu, Quan; Shu, Fuxing; Zhou, Qinian; Shi, Jingshan; Chen, Jishuang (Frontiers in Microbiology, 2020)
The Dendrobium nobile is the only plant which could produce the natural bioactive dendrobine No other source of dendrobine is detected to date except from D. nobile and chemical synthesis. In this study, we aimed to examine the potential fungal endophyte isolated from D. nobile stem segments using molecular method, to detect dendrobine compound through high performance liquid chromatography (HPLC), gas chromatography-mass spectrometry (GC-MS), liquid chromatography with tandem mass spectrometry (LC-MS-MS), and to their metabolite for their antibacterial activity. The potential dendrobine producer strain was recognized as Trichoderma longibrachiatum based on molecular DNA sequencing and GenBank databases. The T. longibrachiatum MD33 produced dendrobine and other compounds in a potato dextrose medium (PDM), as confirmed by HPLC retention time peak analysis. The HPLC results revealed that T. longibrachiatum MD33 biomass showed a peak retention time of 5.28±0.2 min, similar to wild Dendrobium nobile stem dendrobine (5.32±0.2 min) and standard reference dendrobine (5.30±0.2 min), indicating the presence of dendrobine in the fungal biomass. Results of GC-MS and LC-MS analysis revealed that T. longibrachiatum MD33 was produced the same molecular weight (263 in GC-MS and 264.195 in LC-MS) of dendrobine as compared with chemical reference dendrobine and D. nobile dendrobine for strong evidence. Antibacterial activity data revealed that T. longibrachiatum MD33 produced the strongest bactericidal activity against Bacillus subtilis, B. mycoides, and Staphylococcus species, and the diameter of bacterial growth inhibition zone was 12±0.2, 9±0.2, and 8±0.2 mm, respectively. To the best of our knowledge, this is the first study to investigate the T. longibrachiatum as the dendrobine producer and the results revealed that T. longibrachiatum is directly involved in the potential production of similar bioactive compounds as of D. nobile (dendrobine). In addition, the T. longibrachiatum metabolite exhibited potent antibacterial activity and can be a potential strain for medical and industrial purposes.